Assessment of Functional Outcome of Cubitus Varus Deformity Treatment in Children Undergoing Modified French Osteotomy - Dr. Sunil Saharan; Dr. Deepika Rani; Dr. Pankaj Kumar Saini; Dr. Ram Gopal Atal; Dr. Vishnu Sharma (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Cubitus varus is the most common late complication following supracondylar fractures of the humerus in children, primarily resulting from improper fracture reduction and conservative management. Although largely a cosmetic concern, surgical correction is often required to restore anatomical alignment. Modified French osteotomy is among the preferred techniques for its effectiveness and safety. Objective: To assess the functional and radiological outcomes of children with cubitus varus deformity treated using modified French osteotomy. Materials and Methods: This prospective study included 25 pediatric patients with established cubitus varus deformity. The deformity was corrected using the French osteotomy and its modifications, such as a lateral approach without triceps splitting and preservation of the medial cortex. Preoperative evaluation included clinical and radiographic assessment of the carrying angle and range of motion. Postoperative follow-up was conducted at 10 days, 1 month, 2 months, and up to 6 months with emphasis on clinical-radiological parameters including Baumann’s angle, carrying angle, and movement range. Results: The mean age was 10.8 years, with a male predominance (76%). The left elbow was more commonly affected (64%). The average interval between injury and corrective surgery was 2.4 years. Most patients (68%) had severely restricted motion (>20° loss). Postoperative assessment revealed 76% of patients achieved a valgus carrying angle. Excellent outcomes were noted in 60% of patients, fair in 24%, and poor in 16% based on modified Bellemore criteria. The most common complication was residual deformity (16%), followed by lateral elbow bulge (12%) and minor infections (8%). Conclusion: Modified French osteotomy is a reliable, technically feasible, and cosmetically acceptable technique for correcting cubitus varus deformity in children. It provides excellent to fair outcomes in the majority of patients, with a low incidence of complications.